2018
DOI: 10.1021/acsomega.8b00012
|View full text |Cite
|
Sign up to set email alerts
|

Facile Water-Based Strategy for Synthesizing MoO3–x Nanosheets: Efficient Visible Light Photocatalysts for Dye Degradation

Abstract: Nanostructured molybdenum oxides are promising materials for energy storage, catalysis, and electronic-based applications. Herein, we report the synthesis of MoO 3– x nanosheets ( x stands for oxygen vacancy) via an environmentally friendly liquid exfoliation approach. The process involves the reflux of the bulk α-MoO 3 precursor in water at 80 °C for 7 days. Electron microscopy and atomic force microscopy show that the MoO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(83 citation statements)
references
References 74 publications
5
71
0
Order By: Relevance
“…The XRD pattern of the obtained MoO 3− x –CNTs–CC paper (see Figure S1 a in the Supporting Information) indicated that the material was close to amorphous and that the degree of the crystallinity of the MoO 3− x nanosheets was low, in good agreement with previous findings . The peak observed at 14.5° can be assigned to the CNTs–CC matrix beause it was also observed in the XRD pattern of the CNTs–CC paper.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The XRD pattern of the obtained MoO 3− x –CNTs–CC paper (see Figure S1 a in the Supporting Information) indicated that the material was close to amorphous and that the degree of the crystallinity of the MoO 3− x nanosheets was low, in good agreement with previous findings . The peak observed at 14.5° can be assigned to the CNTs–CC matrix beause it was also observed in the XRD pattern of the CNTs–CC paper.…”
Section: Resultssupporting
confidence: 89%
“…[28] The XRD pattern of the obtained MoO 3Àx -CNTs-CC paper (see Figure S1 ai nt he Supporting Information) indicated that the material was closet oa morphous and that the degree of the crystallinity of the MoO 3Àx nanosheets was low,i ng ood agreement with previous findings. [28,29] The peak observed at 14.58 can be assigned to the CNTs-CC matrix beausei tw as also observed in the XRD pattern of the CNTs-CC paper.I nterestingly, the MoO 3Àx -CNTs-CC paper electrodes featured an electronic conductivity of approximately 0.019 Scm À1 ,a sd etermined by using four-point probe measurements. This electronic conductivity value shows that the electrical properties of the www.chemsuschem.org present MoO 3Àx -CNTs-CC paper were comparable to those of previously described MoO 3 -based nanopaper electrodes.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Organic dyes are widely used in textile manufacturing, but they are an environmental threat; hence, the treatment of dyes in wastewater is highly necessary [94]. In general, the degradation rates of rhodamine B (RhB), methylene orange (MO), and methylene blue (MB) are used to evaluate the photocatalytic activity of catalysts.…”
Section: Photodegradation Of Organic Pollutantsmentioning
confidence: 99%